Volatile-assisted intrusion and autometasomatism of leucogranites in the Khumbu Himalaya, Nepal - Weinberg, R; Searle, M (1999)
Leucogranite crops out in the upper Imja Khola, Khumbu Himalaya, Nepal, where it makes up approximately 50% of the exposed bedrock. Leucogranites and their associated aplite-pegmatites typically intruded as concordant sills, millimeters- to kilometers-wide. The exceptional Nuptse granite is an ellipsoidal pluton of nearly 1-km radius, which probably resulted from the ballooning of a sill and is wrapped in concordant country rock foliation. Small-scale structures and mineral paragenesis indicate syntectonic intrusion into high temperature-low pressure sillimanite + muscovite ± cordierite-bearing country rocks. Penetrative deformation of the country rock and sills is characterized by foliation striking N 60°E/40°NW and by north-northwest-plunging mineral lineation subparallel to fold axes of decimeter- to meter-scale isoclinal folds and centimeter- to decimeter-scale kink folds and crenulation. A volatile-rich phase played a fundamental role in the development of the Imja Khola leucogranites. It was responsible not only for pegmatitic rocks but also for autometasomatism producing (1) late growth of poikiloblastic K-feldspar megacrysts; (2) millimeter-wide microveins of albite, which replaced magmatic quartz, plagioclase, and K-feldspar; and (3) growth of tourmaline in schist. The metasomatic origin of K-feldspar poikiloblasts is supported by textural evidence and K/Na and Ba profiles. The volatile-rich phase also played a fundamental role in assisting leucogranite migration. The low viscosity and high pressure of the aqueous phase enabled it to pervade, to disrupt, and to heat up the country rock, giving rise to pathways that permitted the intrusion of the much stiffer magmatic phases.